Dietary Polyphenols and Human Health - Tresserra-Rimbau, Anna (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Polyphenols are a heterogeneous group of bioactive compounds mainly found in plant-based foods. Numerous clinical and epidemiological studies have led to the result that polyphenol intake may protect against chronic diseases such as cardiovascular and neurodegenerative diseases, cancer, or type 2 diabetes, to name some. Polyphenol intake estimation can be obtained through food frequency questionnaires and nutritional biomarkers, both having their own advantages and disadvantages. Although the association between these bioactive compounds and health seems irrefutable, many questions remain still unanswered. For instance, more studies are needed to identify possible interactions and effect-modulating variables, such as smoking habit, body mass index, sex, alcohol, hormones, other foods, etc. Moreover, intestinal microbiota seems to play an important role in the metabolism of polyphenols, but it is still unclear how.